RUANG PUBLIK DAN EKSPRESI POLITIK IDENTITAS: (Studi Tentang Pergulatan Identitas Ke-Papua-an di Yogyakarta) - Moh. Rafli Abbas (Society, 2016)
Study on the dynamics of communities of Papua and its identity. Giddens statement of that identity is a social construction that can be formed in space and time. For the author of the Papua community is a unique community, not only the striking racial differences but they are very ideologically in fighting for his rights in Yogyakarta. This paper tries to answer the question of how the condition of identity of which belonged to someone after constructed? What is done with the collective identity after formed?. This research is the study of the field with a qualitative approach.